2012
DOI: 10.1016/j.biocel.2012.03.016
|View full text |Cite
|
Sign up to set email alerts
|

ER stress is associated with reduced ABCA-1 protein levels in macrophages treated with advanced glycated albumin – Reversal by a chemical chaperone

Abstract: ATP-binding cassette transporter A1 mediates the export of excess cholesterol from macrophages, contributing to the prevention of atherosclerosis. Advanced glycated albumin (AGE-alb) is prevalent in diabetes mellitus and is associated with the development of atherosclerosis. Independently of changes in ABCA-1 mRNA levels, AGE-alb induces oxidative stress and reduces ABCA-1 protein levels, which leads to macrophage lipid accumulation. These metabolic conditions are known to elicit endoplasmic reticulum (ER) str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
3
24
0
3
Order By: Relevance
“…By microarray analysis, we observed that genes intimately related to the ABCA‐1‐mediated cholesterol efflux were selectively altered. We found a reduction in the stearoyl‐Coenzyme A desaturase 1 ( scd ‐1) mRNA level in DM2‐HSA‐treated cells, which could mediate the increase in ER stress and the reduction in ABCA‐1 protein content and cholesterol efflux, as previously demonstrated by our group (Castilho et al, ). In scd ‐1 siRNA‐treated macrophages, a lipid‐induced ER stress response and apoptosis were observed (Erbay et al, ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…By microarray analysis, we observed that genes intimately related to the ABCA‐1‐mediated cholesterol efflux were selectively altered. We found a reduction in the stearoyl‐Coenzyme A desaturase 1 ( scd ‐1) mRNA level in DM2‐HSA‐treated cells, which could mediate the increase in ER stress and the reduction in ABCA‐1 protein content and cholesterol efflux, as previously demonstrated by our group (Castilho et al, ). In scd ‐1 siRNA‐treated macrophages, a lipid‐induced ER stress response and apoptosis were observed (Erbay et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…Our group (Passarelli et al, 2005;Castilho et al, 2012;Machado-Lima et al, 2013) and others (Isoda et al, 2007) have shown that AGE reduce ABCA-1 protein content independent of changes in its mRNA expression. In fact, this reduction was observed in the present study in incubations with DM2-HSA, which affected protein content without changes in mRNA levels.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Endoplasmic reticulum (ER) stress can have marked affects on the immune-stimulatory capacity of antigen presenting cells (1719). Since inhibition of fatty-acid synthesis induces ER stress in neoplastic cells (20), we postulated that TOFA-grown BMDC would exhibit high ER stress.…”
Section: Resultsmentioning
confidence: 99%
“…9) without causing significant changes of ABCA1 mRNA (data not shown). Advanced glycated albumin, which induces ER stress, reduced ABCA1 protein expression without altered ABCA1 transcription in macrophages (48). …”
Section: Discussionmentioning
confidence: 99%